Measurement and control of granular materials : selected peer reviewed papers from the 9th International Conference on Measurement and Control of Granular Materials, MCGM 2011, (Global High Level Academic Seminar), Shanghai, China, 27-29 October, 2011 - Jin, Zhixian, Professor; Xie, Zhi, Professor; Gai, Guosheng (Advanced materials research, 2012)
These are the proceedings of the 9 th International Conference on Measurement and Control of Granular Materials (MCGM' 2011), held on the 27 to 29th October, 2011, in Shanghai, China. The 63 peer-reviewed papers are grouped into the chapters: 1: Flow Measurement and Pneumatic Conveying; 2: Measurement of Size, Volume and Other Parameters; 3: Tomographic Technology, Image Processing and Related Sensors; 4: Powder Explosion and System Protection; 5: New Instruments and Sensor Development; 6: Nano and Powder Materials Preparation; 7: Materials Processing and Preparation; 8:Powder Materials Measur.